1995
DOI: 10.1016/0735-1097(95)00121-f
|View full text |Cite|
|
Sign up to set email alerts
|

Stress echocardiography: Comparison of exercise, dipyridamole and dobutamine in detecting and predicting the extent of coronary artery disease

Abstract: In a clinical setting, exercise echocardiography should represent the first diagnostic approach because it has high diagnostic efficacy and provides additional information on exercise capacity; pharmacologic stress, particularly that of dobutamine, provides a pivotal diagnostic tool when exercise is not feasible or its results are nondiagnostic. Our preliminary data on echocardiographic evaluation at ischemic threshold support the view that myocardial contractility is a major factor in inducing ischemia during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(49 citation statements)
references
References 32 publications
1
44
0
4
Order By: Relevance
“…Dobutamine and exercise stress echocardiographies present similar diagnostic accuracies and are more accurate than dipyridamole stress echo 48 . If dobutamine stress echo does not reveal the presence of residual ischemia in a patient with a history of myocardial infarction, the prognosis is good and the likelihood of another myocardial infarction is low in the perioperative period of a noncardiac surgery 33 .…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 84%
“…Dobutamine and exercise stress echocardiographies present similar diagnostic accuracies and are more accurate than dipyridamole stress echo 48 . If dobutamine stress echo does not reveal the presence of residual ischemia in a patient with a history of myocardial infarction, the prognosis is good and the likelihood of another myocardial infarction is low in the perioperative period of a noncardiac surgery 33 .…”
Section: Dobutamine Stress Echocardiographymentioning
confidence: 84%
“…The maximal double product representing MVO 2 was also greater with exercise than with dobutamine. 20 Although dobutamine echocardiography seems to be quite safe, frequency of side effects observed with exercise echo was lower ( Table 3). The comparison may be made to the study of Elhendy et al 15 comprising a group of 446 hypertensive patients in which the maximal dose of dobutamine (36 Ϯ 7 g/kg/min) and use of atropine (42% patients) were almost the same as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] Dagianti, et al and Casanova, et al showed that the sensitivity of dipyridamole stress echocardiography was 52% and 53%, respectively. 18,19) However, the specificity of dipyridamole echocardiography has been reported to be excellent even in challenging subsets of patients in whom the rate of false-positive responses was higher with electrocardiographic or scintigraphic techniques, such as hypertensive patients. 20) In a pooled analysis of data from 11 published series, the sensitivity and specificity of dipyridamole scintigraphy for CAD detection averaged 85% and 90%, respectively.…”
Section: A B Discussionmentioning
confidence: 99%